Mineral nutrition and yield of sweet potato according to phosphorus doses - Cruz, Sandra Maria da Costa; Cecílio Filho, Arthur Bernardes; Nascimento, Alexsandra Sousa; Vargas, Pablo Forlan (Comunicata Scientiae, 2016)
The sweet potato is a vegetable with potential for expansion of its production area, due to its versatility of use, as it can be used as food, feed and biofuel. However, there is limited information on the mineral nutrition and performance of this vegetable in response to fertilization, especially phosphorus, which is a nutrient with strong interaction with the soil. Given the above, the aim of the present study was to evaluate phosphorus fertilizer levels on growth, mineral nutrition and sweet potato productivity. An experiment carried out from September 3, 2011 until January 3, 2012, in São Luis-MA, aimed to evaluate phosphorus fertilizer levels on growth, mineral nutrition and productivity of sweet potato plants. The experimental design was a completely randomized blocks with four replications. Harvest took place 123 days after seedling transplantation. Phosphorus doses influenced the P level in the soil, plant aerial and root dry matter, total and commercial productivities, and the accumulation of P in the plant aerial part dry matter, tuberous roots and the total plant. The foliar P content was verified to follow a linear adjustment to the doses of P2O5 whereas total and commercial productivities of roots followed a quadratic adjustment. Maximum productivity (1.68 kg m-2) resulted when the P2O5 dose was 191 kg ha-1. The optimal economical dose was 104 kg P2O5 ha-1, that is, 54% of the dose that resulted in the highest commercial productivity.